A SUBSTITUIÇÃO DO TRABALHO VIVO PELO TRABALHO MORTO: UM ESTUDO NOS INTEGRANTES NA REDE DE SERVIÇOS CREDENCIADA DE UMA EMPRESA DO SETOR ELETROELETRÔNICO - Ferreira, Edison (2008)
This study confirmed that there is the substitution of labour for the work alive dead, described by Karl Marx and other important scholars, the EC ABC, eletroeletronic Brazilian company in the sector (segment of the industrial enterprises established in Brazil, responsible for the production of equipment that serve brown line that brings together the products: Televisions, Monitors, Video, Audio, breeding and / or writers of Versatile Disc or video - DVD and compact disc - CD), initially in its National Service Department and then in Posts Services accredited its National Network Services, according to the informatization and change of the model of management of knowledge which led to the which could be leading to a loss of jobs and the Intellectual Capital jobs in the service accredited in Post Services accredited and the loss of quality in the services offered by the PSC to customers and dealers. Adopted is the form of exploratory research of this phenomenon, currently still little examined, in 120 PSC in Brazil.(AU)